Objective Evaluation of the Therapeutic Effects of Oral Steroids in the Management of Biliary Atresia: Therapeutic Effects of Oral Steroids in Biliary Atresia - Mohajerzadeh, Leily; Golverdi, Elahe; Atqiaee, Khashayar; Ebrahimisaraj, Gholamreza; Lotfollahzadeh, Saran; Dara, Naghi; Sarafi, Mehdi; Hosseini, Amirhossein (Iranian Journal of Pediatric Surgery, 2022)
Introduction: Biliary atresia is a progressive fibro-obliterativecholangiopathy that affects both intrahepatic and extrahepatic biliary ducts causing cholestasis and neonatal jaundice. The use of anti-inflammatory agents such as corticosteroids may decrease inflammation and recurrent stricture. Materials and Methods: This clinical trial had been performed on 24 patients admitted to Children’s Hospital with biliary atresia. Prednisolone was not administered in the control group after the operation, but in the intervention group, 2 mg/kg/day of prednisolone was given for 6 weeks and then tapered. Then, its therapeutic effect in the management of biliary atresia was compared. Results: The mean age of the patients in the case and control groups was 2.19 and 2 months, respectively. Cholangitis (P= 0.3), direct hyperbilirubinemia (P= 0.6), ascites (P= 0.5), pigmented stools (P= 0.7), and esophageal varices (P= 0.1) between the two groups was not significant. But the age of the patients, outcome of treatment (P= 0.05), total hyperbilirubinemia (P= 0.05), growth failure (P=0.03), worsening grade of splenomegaly (P= 0.04), hepatomegaly (P= 0.03), fecal pigmentation (P= 0.003), death (P= 0.01), and portal hypertension (P= 0.02) in two groups were significant. Conclusion: Regarding the results, corticosteroids have a significant effect on reducing the bilirubin levels, improving the survival rate, and decreasing the mortality rate, although these results are closely related to the patient’s age at the time of surgery.